The role of schooling for refugees in protracted situations in Malaysia: protection, identity maintenance and acculuturation - Williams, Simon John (2021)
This dissertation investigates the under-researched area of refugee schools in Malaysia that cater to children in protracted positions. With very few scholarly studies on the subject, the researcher sought to explore the role and function of these places of education for the communities they serve. Of specific interest to the study was an understanding of the rationale for communities from the same country (Myanmar) to educate children within separate schools. A literature review outlined a number of research gaps in relation to these schools, which included how protection is defined and managed, the salience of language, faith and culture, and the impact of living in a foreign country for many years.